The influence of iron powder content on the fresh and hardened properties of mortar - Bariza Boukni; Sara Bensalem; Mohamed Lyes Kamel Khouadjia; Oussama Temami; Salim Hamlaoui; Cherif Belebchouche (Przegląd Naukowy Inżynieria i Kształtowanie Środowiska, 2025)
The growing global waste problem, combined with the environmental impact of concrete production, necessitates innovative solutions to mitigate pollution, conserve resources, and enhance concrete performance. This research explores the potential of iron powder (IP) as a partial cement replacement in mortar. The study investigates the influence of iron powder on the fresh and hardened properties of mortar at seven replacement percentages: 1%, 2%, 3%, 4%, 5%, 10%, and 20% by weight. A comprehensive range of tests, including setting times, air content, density, flow time, compressive strength, and flexural strength, were conducted to assess the performance of the IP-modified mortars. The incorporation of iron powder into mortar mixtures significantly affected its properties. For replacement percentages greater than 3%, a slight enhancement in workability (3%) was observed. In terms of compressive strength, optimal performance was achieved with a 5% iron powder replacement (MIP5), surpassing that of the control mortar despite an increase in air content. Further increasing the iron powder content beyond 5% resulted in a modest decrease in compressive and flexural strengths, confirming that 5% is the optimal replacement percentage. This research provides significant practical implications, offering a viable and sustainable pathway for utilizing industrial waste, reducing landfill burden, conserving natural resources, and developing greener, high-performance construction materials.